Pemahaman dan Manfaat dari Sistem Operasi dalam Meningkatkan Kinerja Komputer: Studi Kasus di SMK Mansyaul Huda Tegaldlimo Banyuwangi - Fahimurridho, Ahmad; Syakirin, Muhammad Irham; Fatah, Zaehol (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Advances in computer technology have a significant impact on various areas of life, especially through the role of the operating system as a vital component in the operation of computer devices. The operating system functions as a link between hardware and software, and also helps improve the performance, stability, and security of the system as a whole. This community service activity aims to introduce the basic concepts of operating systems and their benefits in improving computer performance to students of SMK Mansyaul Huda, Tegaldlimo, Banyuwangi. The methods used include interactive lectures, discussions, questions and answers, and demonstrations of operating systems using the VirtualBox application. The effectiveness of the program is measured through student participation and evaluation with quizzes and discussions. The evaluation results showed that 75.8% of participants had a good level of understanding after participating in this activity. This finding shows a significant improvement compared to the initial conditions, where when the first explanation was given, most students did not understand the material at all, and showed confusion about the basic concepts of the operating system. Despite the improvement, some students still had difficulty understanding technical terms in English, such as booting, kernel, and file system. Although practical tools are available, the low initial understanding of students causes the delivery of material to tend to be theoretical and minimal direct application. These findings emphasize the importance of developing more adaptive materials, using simple language, and providing gradual practical support.